METODE PENDIDIKAN RASULULLAH SAW DALAM KITAB AL-TARBIYYAH AL-NABAWIYYAH KARYA ‘UTSMAN QADRIY MAKANISIY - Fahrul Usmi (Jurnal Ilmiah Al-Furqan: Al-qur'an Bahasa dan Seni, 2017)
The research is purposed to study a teaching method applied by Prophet Muhammad SAW by referring to his hadith as stated in the Book al-Tarbiyyah al-Nabawiyyah, written by ‘Utsman Qadriy Makanisiy. Ahmad Tafsir, an expert of Indonesian Islamic education states that the theory and concept of Islamic education must be supported by the Quran verses and hadith for their existences. Therefore, the theory and concept must be built and developed from studying the resources. The topic is studied through library research by using a descriptive and explorative data adapted from a primary data resource, the Book al-Tarbiyyah al-Nabawiyyah, written by ‘Utsman Qadriy Makanisiy. The result of the research concludes that the teaching methods applied by Prophet Muhammad SAW in educating as stated in al-Tarbiyyah al-Nabawiyyah written by ‘Utsman Qadri Makanisiy. It consists of twenty-two methods categorized into two parts; namely macro and micro methods. The Macro method deals with education consisting of thirteen methods. Meanwhile, another method talks about a practice strategy in teaching by which containing nine teaching methods. It is recommended to educators to apply thirteen methods for educating and nine for teaching. All of the methods the prophet applied in the past, had been able to make his fellows be the best generation in the era of prophet Muhammad SAW.